2017
DOI: 10.1136/bmj.j4188
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up brain imaging of 37 children with congenital Zika syndrome: case series study

Abstract: Objective To compare initial brain computed tomography (CT) scans with follow-up CT scans at one year in children with congenital Zika syndrome, focusing on cerebral calcifications. Design Case series study. Setting Barão de Lucena Hospital, Pernambuco state, Brazil. Participants 37 children with probable or confirmed congenital Zika syndrome during the microcephaly outbreak in 2015 who underwent brain CT shortly after birth and at one year follow-up. Main outcome measure Differences in cerebral calcification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
1
30
0
5
Order By: Relevance
“…Postnatal microcephaly and hydrocephalus are examples of this type of slowly evolving injury that may not be detected at the time of a pregnancy ultrasound or at birth. (16, 23, 36, 37) Although ultrasound is an important tool to detect fetal structural brain anomalies, a normal scan cannot be taken as evidence that the fetus has escaped viral injury. Postnatal testing, as recommended by the CDC, is more likely to detect lesser viral injuries through cranial ultrasound imaging (and/or MRI, if feasible), eye examination, auditory screening (i.e.…”
Section: Broadening Spectrum Of Zikv-associated Fetal Injurymentioning
confidence: 99%
“…Postnatal microcephaly and hydrocephalus are examples of this type of slowly evolving injury that may not be detected at the time of a pregnancy ultrasound or at birth. (16, 23, 36, 37) Although ultrasound is an important tool to detect fetal structural brain anomalies, a normal scan cannot be taken as evidence that the fetus has escaped viral injury. Postnatal testing, as recommended by the CDC, is more likely to detect lesser viral injuries through cranial ultrasound imaging (and/or MRI, if feasible), eye examination, auditory screening (i.e.…”
Section: Broadening Spectrum Of Zikv-associated Fetal Injurymentioning
confidence: 99%
“…Magnetic Resonance Imaging (MRI) provides a more detailed assessment of the neurologic manifestations of congenital Zika syndrome, either prenatally or postnatally. However, MRI is often not available in resource-limited settings [20]. MRI findings are similar to US, although MRI provides a clearer delineation of patterns of cortical atrophy, white matter abnormalities related to abnormal myelination, and hypoplasia of the corpus callosum, cerebellum, and brainstem ( Fig.…”
Section: Zika Virus Disease (Zvd)mentioning
confidence: 97%
“…The lower cost of CT and increased availability compared to MRI make it more feasible in resource-limited areas. CT findings of congenital Zika include dystrophic parenchymal calcifications with typical distribution at or below the corticomedullary junction, which decrease in size and number over time [20]. Other findings include secondary effects of global cerebral cortical volume loss, such as ventriculomegaly, discrepancy between cranium and facial size, cranial bone collapse with protuberance of the occipital bone, and small fontanelles [18 • , 20].…”
Section: Zika Virus Disease (Zvd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent studies have indicated that the number of infants and children at risk for Zika-related pathology could be much greater than previously appreciated. In a recent study of 37 children diagnosed with congenital Zika syndrome, brain calcifications were observed in computed tomography scans shortly after birth but had largely diminished or disappeared in follow-up scans taken approximately 1 year later 12 . Strikingly, the resolution of this structural abnormality was not correlated with improved neurological outcomes.…”
mentioning
confidence: 99%